Develovment of literacy teaching materials in elementary schools based on local wisdom in Kuningan - Hanifah, Ifah; Hamidah , Ida; Suntini , Sun; Trang , Ton Thi Thuy; Zulfitriyani, Zulfitriyani (BAHASTRA, 2025)
This study aims to develop literacy teaching materials based on local wisdom for upper-grade elementary school students as a means of supporting the School Literacy Movement. The research addresses the gap in the availability of teaching materials that integrate local wisdom values, particularly in the Kuningan region, which are essential for promoting holistic literacy development. Literacy materials rooted in Kuningan’s local wisdom are crucial, as they enhance students’ understanding by presenting content closely related to their daily lives, such as local culture, traditions, and values. This development research was conducted at SDN 1 Ciloa, SDN Sukaraja, and MI PUI Cilimus in Kuningan. The development process adopted the Joli and Bolitho models, which include stages of needs identification, needs exploration, contextual realization, pedagogical realization, physical production, testing, and product evaluation. Data collection involved both qualitative methods—such as interviews and observations—and quantitative methods from questionnaires and tests. The results reveal four key findings. First, the existing literacy materials do not meet students' needs in terms of design and content. Second, the developed materials are comprehensive, addressing linguistic, cognitive, and socio-cultural dimensions while incorporating complete teaching components. Third, feasibility tests—both theoretical (conducted by experts) and empirical (involving teachers and students)—indicate that the materials are appropriate for use. Fourth, effectiveness testing shows that the materials are effective when implemented in classroom learning. Thus, the developed literacy teaching materials based on local wisdom are not only feasible but also effective in enhancing literacy learning among elementary students in Kuningan.